Examining Types and Duration of Teachers’ Professional Development Activities and Their Relationship with Job Satisfaction - Ilgan Abdurrahman; Basaran Yagmur (Acta Educationis Generalis, 2023)
Introduction: The aim of the study was to describe the teachers’ views on the professional development activities, the frequency of the teachers’ participation to such activities and effectiveness of these professional development (PD) activities. What’s more, it was aimed to analyse the relationship between PD activities that the teachers participated and their job satisfaction (JS).